Experimental Evidence on the Impact of Payments and Property Rights on Forest User Decisions - Rakotonarivo, O. Sarobidy; Bell, Andrew; Dillon, Brian; Duthie, A. Bradley; Kipchumba, Adams; Rasolofoson, Ranaivo Andriarilala; Razafimanahaka, Julie; Bunnefeld, Nils (Frontiers in Conservation Science, 2021)
Clearing forests for swidden agriculture, despite providing food to millions of famers in the tropics, can be a major driver of deforestation. Payments for ecosystem services schemes can help stop swidden agriculture-induced forest loss by rewarding forest users for maintaining forests. Clear and secure property rights are a key prerequisite for the success of these payment schemes. In this study, we use a novel iterative and dynamic game in Madagascar and Kenya to examine farmer responses to individual and communal rights to forestlands, with and without financial incentives, in the context of swidden agricultural landscapes. We find that farmer pro conservation behaviour, defined by the propensity to keep forests or fallows on their lands, as well as the effects of land tenure and conservation incentive treatments on such behaviour, vary across the two contexts. The average percentages of land left fallow in the game are 65% and 35% in Kenya and Madagascar, respectively. Individual ownership significantly improves decisions to preserve forests or leave land fallow in Madagascar but has no significant effect in Kenya. Also, the effect of the individual tenure treatment varies across education and wealth levels in Madagascar. Subsidy increases farmers’ willingness to support conservation interests in both countries, but its effect is four times greater in Kenya. We find no interaction effects of the two treatments in either country. We conclude that the effectiveness of financial incentives for conservation and tenure reform in preserving forestland vary significantly across contexts. We show how interactive games can help develop a more targeted and practical approach to environmental policy.